2011
DOI: 10.1089/jwh.2010.2724
|View full text |Cite
|
Sign up to set email alerts
|

Mammography Adherence: A Qualitative Study

Abstract: Multilevel interventions at the health-care provider and system levels are needed to address barriers women experience to undergoing regular mammography screening. Ultimately, breast cancer screening with mammography is an individual behavior; therefore, individual behavioral change strategies will continue to be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 26 publications
5
45
0
Order By: Relevance
“…There is some literature regarding the possible determinants of this lower participation of immigrant women, such as access to screening services, psychosocial issues and sociocultural factors (Scheppers et al, 2006, Remennick, 2006, Tejeda et al, 2009, Watson-Johnson et al, 2011. However, as far as we are aware, in a setting such as ours, i.e.…”
Section: Introductionmentioning
confidence: 82%
“…There is some literature regarding the possible determinants of this lower participation of immigrant women, such as access to screening services, psychosocial issues and sociocultural factors (Scheppers et al, 2006, Remennick, 2006, Tejeda et al, 2009, Watson-Johnson et al, 2011. However, as far as we are aware, in a setting such as ours, i.e.…”
Section: Introductionmentioning
confidence: 82%
“…Nevertheless, the attendance rates in the counties vary from 71% to 90% (Swedish Breast Cancer Association, 2015); differences have also been found among areas in cities, with attendance rates ranging from 37% to 82% (Zackrisson, Lindström, Moghaddassi, Andersson, & Janzon, 2007). An integrative literature review of earlier studies regarding factors influencing mammographic screening participation has identified a range of reasons, from individual circumstances to more general conditions, such as socioeconomic status and age (Edgar, Glackin, Hughes, Mary, & Rogers, 2013), with many of the studies focusing on non-participation (Achat, Close, & Taylor, 2005; Borda et al, 2011; Brustrom & Hunter, 2001; Fallowfield, Rodway, & Baum, 1990; Gierisch et al, 2009; Johansson & Berterö, 2003; Lagerlund, Hedin, Sparén, Thurfjell, & Lambe, 2000; Lagerlund, Widmark, Lambe, & Tishelman, 2001; Pietrzak, Godlewski, & Adamczak, 2011; Watson-Johnson et al, 2011). This study focuses on the attendees as it could be assumed that continuous participation in mammographic screening is important.…”
Section: Introductionmentioning
confidence: 99%
“…At the individual level, obstacles to care identified have included low education level, 10 poor health literacy, 11 concerns about test efficacy, 12 and language and cultural beliefs related to cancer, distrust, and fear. [13][14][15] Compounded with these concerns, systems barriers such as difficulty accessing highquality diagnostic services, 16 variability in site of care, 17 poor access to primary care physicians or specialists, 18 and lack of insurance, 19,20 can impact adherence to cancer-related care.…”
Section: Introductionmentioning
confidence: 99%